72 Prevalence of Reported and Unreported Vertebral Fractures in Ctpas in Older Adults Above 75 Years. (6th February 2020) - Jones, L; Singh, S; Edwards, C; Goyal, N; Singh, I
Abstract: Introduction: Identifying vertebral fractures is prudent in the diagnosis of osteoporosis as they occur early in this hidden condition. Unfortunately, due to their unspecific presentation, only 25% are clinically recognised. Computerised Tomography Pulmonary Angiogram (CTPA) are frequently requested to confirm pulmonary thromboembolisms, but could also aid in detecting clinically silent vertebral fractures. Current literature suggests that less than one-third of incidental vertebral fractures are reported. The aim of this study is to measure the prevalence of vertebral fractures in CTPA and its relevance to clinical outcomes. Methods: This is retrospective observational study based on the analysis of existing CTPA for acutely unwell patients admitted to medical assessment unit or A & E across three acute sites within Aneurin Bevan University Health board, Wales, UK between January and December 2015. All CTPA reports were reviewed for fragility factures and CTPA images were reassessed for any unreported vertebral fractures. Age and gender were recorded for all patients. Analysis was done for all patients in respect to subsequent fragility fractures and mortality. Difference of proportion test was used to compare two groups with and without vertebral fractures. Results: 179 CTPA were reviewed, 161 patients were included for further analysis. 14.3% (n=23/161) were reported to have a vertebral fracture, however only 8.7% (n=14/161) of reports used the correct terminology of 'fracture'. On subsequent review, an additional 24.2% (n=39/161) vertebral fractures were noted. Therefore, overall prevalence of vertebral fractures was 38.5% (n=62/161). Only 9.1% (n=9/99) of patients without a vertebral fracture developed a subsequent fragility fracture. In comparison, 22.5% (n=14/62) of patients with a previous vertebral fracture sustained a new fragility fracture over next 4 years and this was significantly higher (p = 0.017). Overall mortality over 4 years follow-up was significantly higher for patients with vertebral fractures (64.5%, n=40/62) as compared to those without fractures (43.4%, n=43/99, p = 0.009). Only 48.4% (n=30/62) received osteoporosis treatment. Conclusions: Vertebral fractures could be underreported by radiologists, likely due to human factors as they might be concentrating on the clinical scenario to exclude a pulmonary embolism. However, considering a significant higher mortality in patients with underlying vertebral fracture, it justifies that radiologists could be asked to examine sagittal view in the bone window for possible underlying vertebral fractures, to ensure osteoporosis is treated to guidance.